India's Demographic and Health Transition: A Multi-Source Analysis of Maternal and Child Mortality Trends (1971-2024) - Patel, Prakash (National Journal of Community Medicine, 2026)
Background: India has achieved considerable progress in reducing maternal and child mortality over the past five decades; however, marked inter-state and rural-urban disparities continue to persist. This brief report synthesises national vital statistics from three authoritative sources - the Sample Registration System (SRS) Bulletin 2023, the UN Inter-agency Group for Child Mortality Estimation (IGME) Report 2025, and the UN Maternal Mortality Estimation Inter-Agency Group (UN-MMEIG) Report 2023 - to provide a data-rich, integrated analysis of India's ongoing demographic transition. Key Findings: India's Birth Rate declined from 36.9 per 1,000 population in 1971 to 18.4 in 2023; the Infant Mortality Rate (IMR) fell from 129 to 25 per 1,000 live births over the same period. The Under-5 Mortality Rate declined by 79% since 1990, and the Maternal Mortality Ratio fell by 86% over the same period. High-burden states - including Uttar Pradesh, Chhattisgarh, and Madhya Pradesh - continue to report IMR values of 37 per 1,000 live births, compared to 3 in Manipur and 5 in Kerala. Conclusion: Although India's demographic transition is well advanced at the national level, subnational inequities remain substantial, and targeted public health investment in high-burden states will be essential to achieving SDG 3 targets by 2030.